Comparison of the efficiency and treatment outcome of patients treated with corticotomy-assisted En masse orthodontic retraction with the en masse retraction without corticotomy - Shubham Kumar (Wolters Kluwer Medknow Publications, 2021)
Background: Corticotomy in fixed orthodontic treatment gives a potential approach to reduce the treatment duration. Typically, this duration of rapid tooth movement lasts 4–6 months. Aim: The aim of this study was to compare the treatment outcome and effectiveness in en masse retraction with and without corticotomy. Materials and Methods: Thirty-two patients (male 16 and female 16) who opted to undergo surgery to reduce the orthodontic treatment time were chosen for the research, and the group consisted of 26 patients (male 13 and female 13) who did not opt for the corticotomy procedure were selected as the control. There was no blindness of the party distribution. It was focused on the patient's ability to opt for an additional minor surgical procedure that may affect orthodontic treatment length. The operation was conducted under local anesthesia (Lignox 2%). The same maxillofacial surgeon performed all the surgical operations. Results: The space present in the maxillary and mandibular arch at the time of retraction had no statistically significant difference in both the control and study groups (P > 0.05). In comparison, the mean amount of retraction space in the maxillary arch and maxillary arch was significant in the control and study groups at 1 month, 2 months, 3 months, and 4 months of the time interval. Conclusion: It can be concluded that corticotomy-assisted retraction significantly decreases the total length of orthodontic care. Effectively stationary anchorage segment was made, thereby removing the need for other anchorage boosters, instrumental in maximum anchorage cases using corticotomy technique.